Fatal outcome of malignant transformation of hidradenitis suppurativa: A case report and literature review - Nielsen, Valdemar Wendelboe (Clin Case Rep, 2020)
Squamous cell carcinoma arising in hidradenitis suppurativa (HS) is a rare albeit the most serious complication in HS, with a reported fatality of up to 42.9%. This calls for greater clinical awareness in patients with long‐standing chronic HS.